The Influence Of Price And Product Quality On Customer Loyalty With Satisfaction As An Intervening Variable Among Telkomsel Card Users At Muhammadiyah University Of Pontianak - Lyra Virna Sari; Muhammad Ebuziyya Alif Ramadhan; Sukardi Sukardi (UNIVED Press, 2026)
This study aims to investigate the influence of price and product quality on customer loyalty, with customer satisfaction serving as an intervening variable, among users of Telkomsel prepaid cards. The research adopts an associative approach, involving a total of 100 active students of Muhammadiyah University of Pontianak who use Telkomsel prepaid cards as respondents. The data analysis technique employed is Structural Equation Modeling (SEM), using the SmartPLS 3.0 software.The results of the direct hypothesis testing reveal that both price and product quality have a positive and significant effect on customer satisfaction. Additionally, both customer satisfaction and price have a positive and significant effect on customer loyalty. However, product quality does not have a direct positive and significant effect on customer loyalty. Furthermore, the indirect hypothesis testing indicates that both price and product quality significantly influence customer loyalty through customer satisfaction as a mediating variable.